Working conditions in foundry shops with batch production - A. M. Lazarenkov; I. A. Ivanov (Литьë и металлургия, 2025)
The article presents the results of an assessment of working conditions at various workstations within foundry shops engaged in batch production. The authors identify the occupational hazard classes associated with different sections of these foundries, based on workplace environmental factors and production characteristics